Zmiany terytorialno-organizacyjne archidiecezji gnieźnieńskiej w następstwie Aneksu do bulli cyrkumskrypcyjnej Totus Tuus Poloniae populus z 2004 r. - Krucki, Łukasz (Ecclesia. Studia z Dziejów Wielkopolski, 2014)
In its history which spans more than a millennium the archdiocese of Gniezno not infrequently changed its boundaries due to political and pastoral reasons. It is in this long-term perspective that we should view the papal circumscription bull of 2004 which impacted on the structure and organization of the archdiocese. A reduction of its territory and a diminishing of the number of the faithful to the advantage of the newly founded diocese of Bydgoszcz vitally transformed the profile of the archdiocese. The parishes which remain in the Gniezno archdiocese and those which have been incorporated into it from the archdiocese of Poznań and the diocese of Włocław are rural centres and country towns.